2019
DOI: 10.1080/21632324.2019.1585683
|View full text |Cite
|
Sign up to set email alerts
|

Subjective well-being among communities left behind by international migrants

Abstract: This article assesses the impact of international migration on the subjective well-being of communities of origin in Mexico. Using a representative national survey and an empirical strategy with instrumental variables, we find that higher migratory intensity, at the municipal level, increases life satisfaction among men and women. There is a negative effect on emotional states of women, but an improvement in emotional states of men. Without controlling for schooling, a variable affected by international migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…), eudemonia (referring to fulfillment as a goal for every human being), and affective state (INEGI, 2014). As a result of these strengths, BIARE has been largely used in social sciences when conducting research on well-being, security and leadership (Lara, 2019;Martinez-Martinez et al, 2018). Based on this reliable evidence, a set of dependent, independent, and control variables was obtained from this dataset combined with the World Development Indicators (WDI) from the World Bank.…”
Section: Data and Variablesmentioning
confidence: 99%
“…), eudemonia (referring to fulfillment as a goal for every human being), and affective state (INEGI, 2014). As a result of these strengths, BIARE has been largely used in social sciences when conducting research on well-being, security and leadership (Lara, 2019;Martinez-Martinez et al, 2018). Based on this reliable evidence, a set of dependent, independent, and control variables was obtained from this dataset combined with the World Development Indicators (WDI) from the World Bank.…”
Section: Data and Variablesmentioning
confidence: 99%
“…It became challenging for women to engage in paid work when the majority of house work and field work fall on them. In another study by Lara (2019), migration increases life satisfaction of both men and women but leaves negative effects on the emotional states of only women.…”
Section: Economic Gains and Social Costs Of Migrationmentioning
confidence: 93%
“…This supports results of Singh (2019) that migration, regardless of whether the migrant is a man or woman, typically results in women having higher workloads in both domestic and agriculture. The negative implications of migration in general are felt more by women left behind than men (Lara, 2019;Pandey, 2019).…”
Section: Feminization Of Agricultural Labor and Farm Managementmentioning
confidence: 99%
“…The SWB of those who are left behind is also closely examined. Their SWB is associated with the intensity of emigration in the communities left behind by migrants in Mexico (Lara, 2019). Cortina (2014) found that migration by at least one parent has a negative impact on the life satisfaction of children left behind.…”
Section: Setting and Literaturementioning
confidence: 99%